2016
DOI: 10.1111/rode.12286
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Aid on Total Government Expenditures: New Evidence on Fungibility

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 87 publications
2
2
1
Order By: Relevance
“…In this 9 I acknowledge one reviewer's point about the aid fungibility issue. Unlike the empirical findings of Feyzioglu et al (1998), Marć (2017), and Kaya and Kaya (2020), however, agricultural ODA does not impact government expenditure to agriculture in this case (Appendix S3).…”
Section: Conditionality Of Aid's Impactcontrasting
confidence: 73%
“…In this 9 I acknowledge one reviewer's point about the aid fungibility issue. Unlike the empirical findings of Feyzioglu et al (1998), Marć (2017), and Kaya and Kaya (2020), however, agricultural ODA does not impact government expenditure to agriculture in this case (Appendix S3).…”
Section: Conditionality Of Aid's Impactcontrasting
confidence: 73%
“…An important observation in the top panel of Figure 5 is that government spending increases by less than the amounts of both permanent aid and temporary aid (α P < 1 and α < 1), which makes both permanent and temporary aid fungible. This result is consistent with Chatterjee et al (2012) and Marc (2017) who found that foreign aid increases government spending by less than the amount of aid, even though it is not consistent with my baseline results presented in Figure 2. Chatterjee et al (2012) and Marc (2017) used the same donor-reported aid data used in this robustness exercise, which overestimate the amount of aid that actually goes into recipient countries' budget (Morrissey, 2012).…”
Section: Robustness Checkssupporting
confidence: 71%
“…This result is consistent with Chatterjee et al (2012) and Marc (2017) who found that foreign aid increases government spending by less than the amount of aid, even though it is not consistent with my baseline results presented in Figure 2. Chatterjee et al (2012) and Marc (2017) used the same donor-reported aid data used in this robustness exercise, which overestimate the amount of aid that actually goes into recipient countries' budget (Morrissey, 2012). Donor-reported aid data include a significant amount of aid that is spent by donor countries on services related to the projects financed, which might not be spent inside the recipient country, and do not go into the recipient government's budget.…”
Section: Robustness Checkssupporting
confidence: 71%
See 2 more Smart Citations